Search 83,708 tutors
FIND TUTORS

Michael B.'s Resources

Answers

(2*10^4)x(4*10^5) is the exact same as (2*4)*(10^4*10^5) due to the associative property Obviously 2*4 = 8 When multiplying exponents you add them so... 10^4*10^5 = 10^(5+4) = 10^9 Your answer is then simply 8*10^9 and in the form your question is asking for it will be 8 with 9...

Answers

x2 + 3x + 5 For equations of the form: ax2 + bx + c where a = 1 it will factor to (x + c1)(x + c2) If you multiply that out you'll end up with x2 + c1x + c2x + c1*c2 = x2 + (c1 + c2)x + c1*c2 This means that b = c1+c2...

Answers
(3x^-3*y^-2)^-2 (answer)

Using properties of exponents remember that (xn)m = x(m*n) and x-n = 1/xn So using your equation we have: (3x-3y-2)-2 = 3-2x(-3*-2)y(-2*-2) = (1/9)x6y4

Answers
xy^2/2 * 6x/x^2 (answer)

Since everything is a singular product (it's all multiplied together) you can write it out like this: x(y2/2)*(6x/x2) = x*y2*(1/2)*6*x*(1/x2) Now group your like terms 6*1/2 = 3 x*x*1/x2 = x2/x2 = 1 y2 has no other terms so it simplifies to 3*1*y2 = 3y2  

Answers

From the subject headings you know that this is going to have to be converted into a quadratic equation of the form ax2 + bx + c = 0 So, using the equation you provided, distribute x on the right side x*(x+3) = x2 + 3x and then collect all of your terms on one side...

Answers

Since both sides of the equation are three raised to some power, you can omit the base from the equation entirely. So, 3(2x-1) = 3(x+2) becomes 2x - 1 = x + 2 This is because in order for the two sides to be equal, the exponents on both sides have to be equal as well...

Answers

Remember that (4*102)*(2*103) = (4*2)*(102*103) When you multiply exponents they are added together so the problem becomes 8*10(2+3) = 8*105 = 800000 In fact, if you notice the other two numbers are powers of the base 2 so the problem can actually be thought of like this: (22*102)*(21*103)...

Answers
3x^2 +2x -16 =0 (answer)

3x2 + 2x - 16 = 0 a = 3 b = 2 c = -16 x = [-b ± √(b2 - 4ac)]/2a b2 - 4ac = 4 - (4*3*-16) = 196 x = (-2 ± √196)/6 x = (-2 + 14)/6 = 12/6 = 2 x = (-2 - 14)/6 = -16/6 = -8/3 Check your solutions by plugging them back in to the original...

Answers

Substitution means that you take one equation and put the variables in terms of each other, then you substitute that value in for the other variable in the remaining equation. Since there are two equations in two variables you can substitute 4 total ways. Using your equations: 3x - y...

Answers

For 4 perfect exam scores Sergio would have had 400 total points, as it was he ended up with 70% of those points or 0.7*400 = 280 points By dropping a test grade Sergio reduced the number of possible points to 300 and his grade improved to 80% 0.8*300 = 240 points The difference...

Answers
Story problem (answer)

This type of motion is described as projectile motion, ideally in one dimension meaning that the rocket is going straight up and straight down. The equation for motion in one direction is given by d = vit + (1/2)at2 where d is the displacement vi = initial velocity a = acceleration t...

Answers
3(x-2)+5x=10 (answer)

3(x-2) + 5x = 10 The first step is to recognize that 3(x-2) = 3*x - 3*2 = 3x - 6 So putting that back in to the equation it's 3x - 6 + 5x = 10 Now add like "x" terms on the left side and add 6 to both sides 8x - 6 + 6 = 10 + 6 8x = 16 Divide...

Answers

3r2 + 8r -3 Where a = 3 b = 8 c = -3 You use the product of a*c = -9 Now ask yourself what factors of -9 could add up to 8? it's gonna be 9 and -1 so you write that out in place of 8r 3r2 + 9r - 1r -3 Now separate your common terms 3r(r + 3) -...

Answers

In essence, it accounts for the number of particles that can occur in "ideal" solutions. The typical definition is that it is the ratio of the actual concentration of particles in solution to the concentration of the solute as calculated by its mass. So for non-ionic compounds in solution,...

Answers

Place the decimal after the first non-zero digit and then count the number of spaces to determine how much to raise ten by an exponent. In your example: 5 3030000 You have 7 decimal places after the first number and you have to include up to the last non zero number after that. So...

1 2 3 4